Global and National Socioeconomic Disparities in Obesity, Overweight, and Underweight Status - Spencer Moore; Justin N. Hall; Sam Harper; John W. Lynch (Hindawi Limited, 2010)
Objective. To examine the association between socioeconomic factors and weight status across 53 countries. Methods. Data are cross-sectional and from the long version of the World Health Survey (WHS). There were 172,625 WHS participants who provided self-reported height and weight measures and sociodemographic information. The International Classification of adult weight status was used to classify participants by body mass index (BMI): (1) underweight (<18.5), (2) normal weight (18.5-24.9), (3) overweight (25.0-29.9), and (4) obese (>30.0). Multinomial regression was used in the analyses. Results. Globally, 6.7% was underweight, 25.7% overweight, and 8.9% obese. Underweight status was least (5.8%) and obesity (9.3%) most prevalent in the richest quintile. There was variability between countries, with a tendency for lower-income quintiles to be at increased risk for underweight and reduced risk for obesity. Conclusion. International policies may require flexibility in addressing cross-national differences in the socio-economic covariates of BMI status.